Loss of Gn1a/OsCKX2 confers heavy‐panicle rice with excellent lodging resistance. Issue 1 (21st January 2022) - Tu, Bin; Tao, Zhang; Wang, Shiguang; Zhou, Lei; Zheng, Ling; Zhang, Chun; Li, Xinzi; Zhang, Xiaoyu; Yin, Junjie; Zhu, Xiaobo; Yuan, Hua; Li, Ting; et al.
Abstract: Significant achievements have been made in breeding programs for the heavy‐panicle‐type (HPT) rice ( Oryza sativa ) in Southwest China. The HPT varieties now exhibit excellent lodging resistance, allowing them to overcome the greater pressures caused by heavy panicles. However, the genetic mechanism of this lodging resistance remains elusive. Here, we isolated a major quantitative trait locus, Panicle Neck Diameter 1 ( PND1 ), and identified the causal gene as GRAIN NUMBER 1A/CYTOKININ OXIDASE 2 ( Gn1A/OsCKX2 ). The null gn1a allele from rice line R498 ( gn1a R498 ) improved lodging resistance through increasing the culm diameter and promoting crown root development. Loss‐of‐function of Gn1a/OsCKX2 led to cytokinin accumulation in the crown root tip and accelerated the development of adventitious roots. Gene pyramiding between the null gn1a R498 allele with two gain‐of‐function alleles, STRONG CULM 2 ( SCM2 ) and SCM3, further improved lodging resistance. Moreover, Gn1a/OsCKX2 had minimal influence on overall rice quality. Our research thus highlights the distinct genetic components of lodging resistance of HPT varieties and provides a strategy for tailor‐made crop improvement of both yield and lodging resistance in rice. Abstract : Loss of Gn1a/OsCKX2 confers heavy‐panicle rice with excellent lodging resistance by increasing culm and crown root development. Moreover, Gn1a/OsCKX2 had minimal influence on overall rice quality. This research provides a strategy for tailor‐made improvement of yield and lodging resistance in rice.